2013
DOI: 10.1257/aer.103.3.263
|View full text |Cite
|
Sign up to set email alerts
|

Is Ignorance Bliss? The Effect of Asymmetric Information between Spouses on Intra-Household Allocations

Abstract: We conducted a field experiment in Southern Ghana to test the effect of asymmetric information on intrahousehold allocation. A lottery was conducted, where prizes were distributed in public and in private. The results indicate that asymmetric information over windfalls has a differential effect on observable and concealable expenses, consistent with hiding. Husbands' public windfalls increase investment in assets and social capital, while there is no such effect when wives win. Private windfalls of both spouse… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
33
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 79 publications
(36 citation statements)
references
References 4 publications
3
33
0
Order By: Relevance
“…3 One key difference in co-operative and non-co-operative models is the stability of the bargaining outcome: co-operative models are presumed stable in the absence of any changes to the spouses’ relative bargaining power, while non-co-operative equilibria may shift as new information about the spouse’s position and strength becomes available. Results consistent with non-co-operative bargaining models have now been observed across a range of developing country contexts (e.g., Katz, 1995, Kebede et al, 2013, Mabsout and Staveren, 2010, Malapit and Quisumbing, 2014, McPeak and Doss, 2006, Udry, 1996, Castilla and Walker, 2013), emphasizing the potential for shifts in women’s decision-making authority to lead to shifts in welfare and other outcomes for women and households.…”
Section: Intra-household Bargaining and Decision-making Authoritysupporting
confidence: 56%
“…3 One key difference in co-operative and non-co-operative models is the stability of the bargaining outcome: co-operative models are presumed stable in the absence of any changes to the spouses’ relative bargaining power, while non-co-operative equilibria may shift as new information about the spouse’s position and strength becomes available. Results consistent with non-co-operative bargaining models have now been observed across a range of developing country contexts (e.g., Katz, 1995, Kebede et al, 2013, Mabsout and Staveren, 2010, Malapit and Quisumbing, 2014, McPeak and Doss, 2006, Udry, 1996, Castilla and Walker, 2013), emphasizing the potential for shifts in women’s decision-making authority to lead to shifts in welfare and other outcomes for women and households.…”
Section: Intra-household Bargaining and Decision-making Authoritysupporting
confidence: 56%
“…Castilla and Walker () use goods as well as money in a region of southern Ghana where the implicit rules of marriage mean that husbands must provide cash in the form of ‘chop money’ to their spouses to cover the daily costs of the household. The wives choose how this money is spent and whether to divert some of the money into private goods.…”
Section: Information and Hidingmentioning
confidence: 99%
“…Some have suggested that women's use of rotating savings and credit organizations (ROSCAs) in Kenya is consistent with income hiding (Andersen and Balland 2002), and spouses have been shown to spend money differently when it arrives in secret in Ghana (Castilla and Walker (2013a and 2013b), Niger (Aker et al (2014)), and the Philippines (Ashraf (2009)). Spouses invested significant resources in obtaining information about their spouse's finances in Kenya (de Laat (2008)).…”
Section: Literature Reviewmentioning
confidence: 99%